(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
Editorial Board Carl Burkart (Co-Editor) Deb Carr (Guest Editor) Alexa Collesides (Editorial Team Member) Ruud Duvekot (Co-Editor) Susan Forseille (Co-Editor) Amy Giaculli (Associate Editor) Alan Mandell (Founding Co-Editor) Nan Travers (Founding Co-Editor) Don Presant (Guest Editor) Serge Ravet (Guest Editor)